2019
DOI: 10.1186/s12862-019-1510-4
|View full text |Cite
|
Sign up to set email alerts
|

Geographic isolation and climatic variability contribute to genetic differentiation in fragmented populations of the long-lived subalpine conifer Pinus cembra L. in the western Alps

Abstract: Background Genetic processes shape the modern-day distribution of genetic variation within and between populations and can provide important insights into the underlying mechanisms of evolution. The resulting genetic variation is often unequally partitioned within species’ distribution range and especially large differences can manifest at the range limit, where population fragmentation and isolation play a crucial role in species survival. Despite several molecular studies investigating the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 106 publications
4
22
0
3
Order By: Relevance
“…It was interesting to note that the monomorphic profiles in two loci (Ach45 and Ach54) were evidenced in the southernmost population sampled in this study (Los Lagos Region). Based on the last glacial maximum (LGM) Patagonian ice sheet range (Moreno et al, 2018), we hypothesize that colonization event of Los Lagos population took place more recently than those populations northward, leading to a loss of alleles and decreased genetic diversity southward this region, explained by genetic drift (Hewitt, 2004;Gugerli et al, 2009;Tóth et al, 2019). However, this genetic pattern remains to be studied, and new northern-and southernmost populations of A. chilensis should be considered in order to define possible refugia of this species during LGM period.…”
Section: Resultsmentioning
confidence: 99%
“…It was interesting to note that the monomorphic profiles in two loci (Ach45 and Ach54) were evidenced in the southernmost population sampled in this study (Los Lagos Region). Based on the last glacial maximum (LGM) Patagonian ice sheet range (Moreno et al, 2018), we hypothesize that colonization event of Los Lagos population took place more recently than those populations northward, leading to a loss of alleles and decreased genetic diversity southward this region, explained by genetic drift (Hewitt, 2004;Gugerli et al, 2009;Tóth et al, 2019). However, this genetic pattern remains to be studied, and new northern-and southernmost populations of A. chilensis should be considered in order to define possible refugia of this species during LGM period.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Guizado et al [29] characterized the Peruvian rosewood using ISSR markers and found higher variations within populations (98.1%) than among (1.9%) populations. A previous study concluded that long-term natural selection and geographical isolation allowed the local population to conserve a specific genotype, thereby increasing the genetic variations between populations [51]. STRUCTURE, neighbor-joining analysis, and PCoA were used as clustering algorithms to elucidate the population structure of Peruvian rosewood germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Populations in the peripheral mountain massifs are sporadic and sparse. P. cembra is a long-lived species (>500 years) with long generation intervals, which can maintain stable population size over long periods of time without inbreeding depression and preserve high amount of genetic variation (Gugerli et al 2009;Toth et al 2019). The species produces heavy seeds that are exclusively dispersed by a mutualistic bird (Nucifraga caryocatactes L., spotted nutcracker) specialized in extracting seeds of P. cembra from its non-opening cones and in caching seeds in soil far from the treemother (Crocq 1990).…”
Section: Study Speciesmentioning
confidence: 99%